Digital blocks with and without adrenalin: A randomised-controlled study of capillary blood parameters - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2008)
This study compared fingertip capillary blood gas parameters before and after digital anaesthesia using lidocaine with and without Adrenalin. Twenty patients who underwent surgery on their fingers under digital ring block anaesthesia were randomly anaesthetised with 2% lidocaine or 2% lidocaine with 1:80,000 Adrenalin. Capillary blood parameters were measured prior to the digital blocks and 15 minutes after the injections. In the plain lidocaine group, PO2 and SaO(2) increased significantly after injection (P = 0.025 and 0.017, respectively). In the lidocaine with Adrenalin group, PO2 and SaO(2) decreased after the injections. However, this decrease was not statistically significant. Patients in the plain lidocaine group had return of sensation to the finger tip 4.8 (+/- 0.6) hours after the operation. This period was 8.1 (+/- 0.8) hours for the lidocaine with Adrenalin group.
Keywords: digital anaesthesia; Adrenalin; digital ischaemia; digital necrosis; ELECTIVE EPINEPHRINE USE; ANESTHESIA; FINGER; MYTH